Implementasi Sistem Computer-Assisted Test (CAT) untuk Meningkatkan Efisiensi Evaluasi Belajar di Lembaga Bimbingan Belajar Graha Taruna Aceh - Al Bahri; Safrizal Safrizal; Aulia Rahman (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The Computer-Assisted Test (CAT) system represents a practical application of information technology aimed at improving the efficiency and accuracy of learning evaluation processes. This study aims to implement and evaluate a web-based CAT system at Graha Taruna Aceh Tutoring Institution. The research methodology includes system design and implementation, followed by evaluation through functional testing and a user perception survey. The results indicate that the CAT system enhances the efficiency of examination administration, improves scoring transparency, and facilitates the management of test items and examination results, while also generating significant operational cost savings, with an average cost reduction of approximately 60% per examination session compared to conventional methods. The implementation of this system further contributes to increased utilization of information technology within non-formal educational institutions.